Educate Children's Character With Finding Nemo Film Media - Patria, Rida (EDUPEDIA Publisher, 2023)
Children as the next generation of the nation, need to get serious attention, because the progress of a country will depend on the current and future generations. In this article, the author will conduct a review of an animated children's film Finding Nemo as a positive viewing medium to educate children's character as the nation's successor. Finding Nemo is a computer graphic animated film made in the United States which won an Academy Award. Released on May 30, 2003 in Canada and the United States. The main players are Albert Brooks, Ellen DeGeneres, Alexander Gould, Willem Dafoe, and many more. The director is Andrew Stanton. The method used in this research is descriptive-analytical method, in which the researcher describes all the data or conditions of the subjects or research objects and then analyzes them by explaining all the aspects contained in the film in the form of dialogue. One of the most important moral messages in this film is the importance of following the advice of parents.